Self-Organization and Information Processing: From Basic Enzymatic Activities to Complex Adaptive Cellular Behavior - De la Fuente, Ildefonso M.; Martínez, Luis; Carrasco-Pujante, Jose; Fedetz, Maria; López, José I.; Malaina, Iker (Frontiers in Genetics, 2021)
One of the most important goals of Contemporary Biology is to understand the origin of the molecular order that underlies the complex dynamic architecture of cellular life. Here we present an overview of the main sources of biomolecular order and complexity spanning from the most elementary levels of molecular activity to the emergence of cellular systemic behaviors. First we have addressed the dissipative self-organization, the main driving force of molecular order in the cell. Extensive studies over the last four decades have shown that self-organization is central to understand enzyme activity under cellular conditions, functional coordination between enzymatic reactions, the emergence of dissipative metabolic networks, and molecular rhythms. The second fundamental source of order is the molecular information processing. Studies on effective connectivity based on Transfer Entropy have made possible the quantification in bits of biomolecular information flows in dissipative metabolic networks. This information processing enables an efficient self-regulatory control of metabolism. As a consequence of both main sources of order, systemic functional structures emerge in the cell; in fact, quantitative analyses with dissipative metabolic networks have shown that the basic units of life display a global enzymatic structure that seems to be an intrinsic property of the functional metabolism as a whole. This systemic metabolic structure is verified experimentally in both prokaryotic and eukaryotic cells. Here we also have analyzed using advanced tools of Statistic Mechanics and techniques of Artificial Intelligence how the study of systemic dissipative metabolic networks has shown the emergence of Hopfield-like dynamics which are characterized by exhibiting associative memory. We have recently confirmed this thesis by testing the appearance of associative conditioning behavior in individual amoeba cells. In these Pavlovian-like experiments, several hundreds of cells were able to learn new systemic migratory behaviors and remember them over long periods relative to their cell cycle, forgetting them later. Such associative process seems to correspond to epigenetic memory. The cellular capacity of learning new adaptive systemic behaviors represents a fundamental evolutionary mechanism for cell adaptation.